Sosialiasasi Pemilih Pemula 2020 pada Pilkada di Tengah Pandemi Covid-19 di SMA dan SMK Wisnuwardhana Malang - wahyu Hindiawati; Rika Novitasari; Tikka Dessy Harsanti; Erifano Dimas Ramadhan; Pipit Izatul Masruroh (PT.Mantaya Idea Batara, 2022)
General election or what is often abbreviated as Election is the process of selecting people to fill certain political positions. These positions are varied, ranging from president, people's representatives at various levels of government, to village heads. At the local level, the means of implementing democracy are called regional head elections or pilkada. Beginner Voters are the basis of voters who use their rights for the first time in the 2020 simultaneous elections. In this community service, the aim is to provide socialization to Wisnuwardhana Malang High School students about the 2020 Beginner Voters